The traitor's blade - Sands, Kevin (Sands, Kevin. Blackthorn key (Series), 2022)
Christopher, Tom, and Sally have returned to London, but their problems aren't over yet. A friend is ambushed and left for dead, and an anonymous letter arrives at Blackthorn containing a riddle and a secret code. Soon, Christopher and his friends realize they've uncovered a plot to kill the king, and they're the only ones who can stop it.